A Connecticut Yankee in King Arthur's Court. - Twain, Mark (First Avenue Classics Ser., 2015)
Hank, a 19th-Century New England factory manager, suffers a blow to the head that sends him back in time to medieval England. Determined to make the best of the situation, the Yankee attempts to modernize England, setting up schools and factories while trying to hide what he's doing from the Catholic Church and the British monarchy. This American novel written by humorist Mark Twain satirizes the idealized notions of the Middle Ages made popular by other writers of the time. This unabridged version of Twain's comedy, first published in 1889, includes illustrations by Daniel Carter Beard.